An approach to curriculum integration of ict - Orjuela Forero, Dora Lidia (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The main focus of the theoretical review of this article is the curricular integration of Information and Communication Technology (ICT). We examine the conceptualization, levels and models of integration of ICT, as well as provide some suggestions for its implementation in an educational institution. We also narrate an experience of curriculum integration of ICT in a specific primary and secondary level educational institution, examining its scope, opportunities and impact.